Prediction of the weld shape in arc welding: A numerical modeling example in multiphysics coupling - Roger, Frédéric; Van, Ky Dang (European Journal of Computational Mechanics, 2004)
A numerical model of the arc welding process is presented. It deals with all arc welding process with and without filler metal (Gas Metal Arc Welding and Gas Tungsten Arc Welding). We consider the three dimensional modelling of the stationary weld pool with a free deformable surface. All coupled equations are solved by the finite volume method. We consider heat transfer ands fluid flow in the weld pool and the geometry of the free surface subjected to arc pressure and drop impact in GMAW. The location of the energy supplied by drops in the weld pool is assumed to be a function of the Weber number. Comparison with macrography shows a really good agreement of the model.